Archaeal lipids - Řezanka, Tomáš; Kyselová, Lucie; Murphy, Denis J (Progress in lipid research, 2023)
The major archaeal membrane glycerolipids are distinguished from those of bacteria and eukaryotes by the contrasting stereochemistry of their glycerol backbones, and by the use of ether-linked isoprenoid-based alkyl chains rather than ester-linked fatty acyl chains for their hydrophobic moieties. These fascinating compounds play important roles in the extremophile lifestyles of many species, but are also present in the growing numbers of recently discovered mesophilic archaea. The past decade has witnessed significant advances in our understanding of archaea in general and their lipids in particular. Much of the new information has come from the ability to screen large microbial populations via environmental metagenomics, which has revolutionised our understanding of the extent of archaeal biodiversity that is coupled with a strict conservation of their membrane lipid compositions. Significant additional progress has come from new culturing and analytical techniques that are gradually enabling archaeal physiology and biochemistry to be studied in real time. These studies are beginning to shed light on the much-discussed and still-controversial process of eukaryogenesis, which probably involved both bacterial and archaeal progenitors. Puzzlingly, although eukaryotes retain many attributes of their putative archaeal ancestors, their lipid compositions only reflect their bacterial progenitors. Finally, elucidation of archaeal lipids and their metabolic pathways have revealed potentially interesting applications that have opened up new frontiers for biotechnological exploitation of these organisms. This review is concerned with the analysis, structure, function, evolution and biotechnology of archaeal lipids and their associated metabolic pathways.
Keywords: ethery; membránové lipidy; Ethers; Bacteria; Archaea; terpeny; Membrane Lipids; Terpenes